Aguirre to issue lookout bulletin for Faeldon - Ramos, Marlon (2017)
Justice Secretary Vitaliano Aguirre II on Wednesday said that he would issue a lookout travel order against former Customs Commissioner Nicanor Faeldon and his former colleagues to ensure their participation in the investigation of the smuggling of P6.4-billion "shabu" (crystal meth) shipment.
Keywords: Aguirre, Vitaliano II; Faeldon, Nicanor E; Drug smuggling